The Role of Sharia-Compliant Financial Institutions in Promoting Economic Stability: Insights from Recent Scholarly Contributions - Nazori, Nazori; Rafidah, Rafidah; Mubyarto, Novi; Mutia, Agustina; Rosmanidar, Elyanti (International Journal of Economics (IJEC), 2024)
This research examines the role of Islamic financial institutions in promoting economic stability through a literature study of recent scholarly contributions. Islamic financial institutions are seen as alternative financial instruments that operate under Islamic principles, which prohibit usury, excessive speculation, and non-transparent activities. This research aims to understand the mechanisms used by Islamic financial institutions in creating economic stability and evaluate the latest empirical evidence supporting such contributions. The research method used is a literature study with a qualitative approach, where various journals and research reports on Islamic finance, economic stability, and monetary policy are reviewed and analysed. The results show that Islamic financial institutions play an important role in economic stability through asset-based financing, portfolio diversification, as well as the application of risk management in accordance with Islamic principles. This research contributes to providing policy makers, academics, and financial practitioners with a deeper understanding of the potential of Islamic financial institutions as instruments that can strengthen economic stability.